Design and characterization of electrode materials for lithium-ion and lithium-oxygen batteries based on ZIF-67 template - Guo, Yuanyuan (2019)
Metal-organic frameworks (MOFs) have been achieving increasing attention in various areas including energy storage, catalysis and chemical sensing because of their large surface area, high porosity, chemical tunability and designable structure. As one kind of MOFs, Co-based zeolitic imidazolate framework (ZIF-67) with cobalt ions as metal nodes and N-containing methyl-imidazole as organic ligands possesses good chemical and thermal stability as well as high surface area up to 1300 m2 g-1. N-rich ligands could bring the incorporation of nitrogen in the resultant carbon matrix, which could enhance the energy storage ability. ZIF-67 has been considered to be effective template or precursor to construct novel porous architectures with intriguing properties in Li-ion and Li-O2 batteries. In this thesis, I first explore a strategy to confine the small sized Sn nanoparticles into a porous carbon framework based on ZIF-67 as template. For the high energy density lithium ion batteries, Sn has been known as a potential anode alterative because of its high specific capacity. However, preparation of small sized Sn nanoparticles still needs to be improved. And aggregation of Sn nanoparticles is still a problem for Li-ion batteries, which will cause the capacity fading. So it is important to develop a unique method to synthesize Sn nanoparticles with good stability. In this thesis, a porous carbon framework was derived from ZIF-67 firstly. Then it was immersed into SnCl4·5H2O solution allowing tin ions diffuse into the channels of the carbon frameworks followed by sodium borohydride reduction. In this way, the ultra-small Sn nanoparticles can be confined into the pores of carbon networks. The carbon frameworks not only suppress the aggregation of Sn nanoparticles but also increase the electrical conductivity of the Sn@ carbon electrode. Interestingly, the obtained Sn@ carbon composites showed the obvious improvement in specific capacity and cycling stability (740 mAh g-1 with a current of 200 mA g-1 over 200 cycles) as anode for Li-ion batteries comparing with pure Sn and carbon. The present results provide opportunity to the development of energy storage materials using ZIF-67 as template. Inspired by the first study, the application of ZIF-67 was extended to synthesize the cobalt and nickel layered double hydroxide (Ni-Co LDH), which will be considered as the oxygen evolution reaction (OER) catalyst for Li-O2 batteries. In order to improve the reaction kinetics, it is critical to develop porous catalyst, which could facilitate the O2 diffusion through the electrode and result in many catalytically active sites. Via solvothermal treatment with Ni(NO3)2 solution, ZIF-67 can be transferred into much porous Ni-Co LDH. During this process, ZIF-67 acted as the sacrificial template not only providing cobalt precursor but also leading to the generation of porosity in Co-Ni LDH. The experimental results have shown the good catalytic ability in Li-O2 batteries. More importantly, after discharge of the prepared Co-Ni LDH, small CoxNiy alloy nanoparticles (around 10 nm) can be prepared, which were embedded into LiOH networks. Remarkably, CoxNiy alloy nanoparticles exhibited excellent catalytic activity with a very low charge potential (3.3 V), which is comparable to the noble metal catalyst. ZIF-67 brought us a hope to the development of small size non-precious metal catalysts with super catalytic ability for Li-O2 batteries.